ANALISIS KETERAMPILAN ANAK MENUMBUHKAN PERCAYA DIRI MELALUI METODE CERITA PADA KELOMPOK B PAUD KI ALI CILEGON - Tati Masliati (LPPM Universitas Bina Bangsa, 2024)
Self-confidence is an important thing that children need to have in order to be able to climb the wheel of life. From the observation results, it is known that the problems are that children do not dare to come forward, children are afraid to speak in front of their friends, children always complain during every lesson, children do not communicate enough with their friends. friends. environmental people In this research the formulation of the problem is how to increase students' self-confidence by using the PAUD Ki Ali storytelling method in group B. The approach used is a quantitative approach after carrying out a pre-test in one group. The information used in this research was obtained from observations of children. The data collection method for this research is pre-test and post-test. The results showed that the average self-confidence of group B PAUD Ki Ali Cilegon in the story method was 29.02 before the test and 37.24 after the test based on the average of the children. , we get ????????????????????????= ????(1−????, ????−1) = ????(0.95)(16) = 1.746, so we get the value ????ℑ????. ???????????? is worth 10.27 > 1.746 so ???????? is rejected and Ha is accepted. So it can be concluded that the use of the story method can increase the self-confidence of PAUD Group B Ki Ali Cilegon students. It is hoped that teachers will apply this narrative method to increase students' self-confidence. The story method used by researchers is a story of friendship between an ape and a turtle